Quality of Reporting and Risk of Bias of Randomized Clinical Trials Published in Spanish and Latin American Journals [Calidad del Reporte y Riesgo de Sesgo de Los Ensayos Clínicos Aleatorizados Publicados en Revistas de España y Latinoamérica] - Bachelet-Norelli, V (Medwave Estudios Ltda, 2019)
[No abstract available]